Oral form discrimination and alternate articulatory motion rate in the cerebral palsied - Roshni Ray (Journal of All India Institute of Speech and Hearing)
The present investigation was undertaken in light of the continuing search and need for answers regarding the possible relationship between oral sensorymotor efficiency and speech proficiency. This study sought to explore the oral sensory and motor abilities of 35 subjects (20 normals and 15 cerebral palsied) in the age of 4-12 years.